Organizational and pedagogical aspects of the formation of information competence of the future translator - Тарасенко, Ростислав (Pedagogy of Higher and Secondary Education, 2014)
Tarasenko R. A. Organizational and pedagogical aspects of the formation of information competence of the future translator The article deals with problems of information competence of future translators and its formation based on core competencies. Means of formation of information competence of future translators and interpreters in accordance with the concept of a world education and relevant to the national education system are provided.